2017
DOI: 10.1101/234427
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A tissue-specific self-interacting chromatin domain forms independently of enhancer-promoter interactions

Abstract: A variety of self-interacting domains, defined at different levels of resolution, have been described in mammalian genomes. These include Chromatin Compartments (A and B)1, Topologically Associated Domains (TADs)2,3, contact domains4,5, sub-TADs6, insulated neighbourhoods7 and frequently interacting regions (FIREs)8. Whereas many studies have found the organisation of self-interacting domains to be conserved across cell types389, some do form in a lineage-specific manner6710. However, it is not clear to what d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 37 publications
4
29
0
Order By: Relevance
“…This is consistent with the observed additive effects of individual enhancers at the globin (5, 7) and many other genes (6). Importantly, we have previously shown that no single enhancer element in the a-globin locus is critical for the formation of the chromatin structures associated with active a-globin transcription (3,5). The formation of complexes in which multiple enhancers and promoters interact simultaneously therefore provides a structural basis for the observed functional cooperativity and also suggests a role for apparent redundant enhancer elements (8,9).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with the observed additive effects of individual enhancers at the globin (5, 7) and many other genes (6). Importantly, we have previously shown that no single enhancer element in the a-globin locus is critical for the formation of the chromatin structures associated with active a-globin transcription (3,5). The formation of complexes in which multiple enhancers and promoters interact simultaneously therefore provides a structural basis for the observed functional cooperativity and also suggests a role for apparent redundant enhancer elements (8,9).…”
Section: Discussionsupporting
confidence: 88%
“…The globin loci, which provide ideal models to elucidate the general principles of mammalian gene regulation, have been extensively studied in this way. For example, we have previously shown that the active mouse a-globin cluster and its regulatory elements are located in a decompacted ~70 kb chromatin domain that forms early in erythroid differentiation and is flanked by CTCFbinding sites (2)(3)(4). Within this domain, the a-globin genes interact with five enhancer elements, which cooperate in an additive manner to upregulate gene expression (5).…”
Section: Introductionmentioning
confidence: 99%
“…HoxD10/Dlx2 loci and a second set for similarly interacting polycomb target genes, Nkx2-3/Pax2 ( Figure S7), and performed non-denaturing RASER-FISH (Brown et al, 2018) to measure the three-dimensional distance between these loci in individual cells ( Figures 6B, S6C, and S7A). This revealed a distribution of distances in cells where cohesin is intact, including some in close proximity ( Figures 6C, S6D, S7B, and S7D).…”
Section: Polycomb Chromatin Domain Interactions Are Disrupted By Cohesinmentioning
confidence: 99%
“…RASER-FISH was conducted as previously described (Brown et al, 2018) with minor changes. Briefly, cells were grown on coverslips, labeled for 24 h with BrdU/BrdC mix (3:1) at final conc.…”
Section: Fish Raser (Resolution After Single-strand Exonuclease Resecmentioning
confidence: 99%
“…One characteristic of an active enhancer is that it physically contacts the promoter of the gene it regulates [42][43][44][45]. To test whether this was true for these putative enhancers, we performed next generation Capture-C to identify regions interacting with the promoters of PROM1 and TAPT1.…”
Section: Prom1 Is Regulated By H3k79me2/3 Enhancersmentioning
confidence: 99%